2022
DOI: 10.29303/jku.v11i1.641
|View full text |Cite
|
Sign up to set email alerts
|

Hipertensi Sebagai Determinan Utama untuk Peningkatan Risiko Stroke pada Populasi Penduduk di Daerah Pesisir

Abstract: Hipertensi merupakan determinan utama untuk terjadinya stroke pada populasi penduduk di daerah pesisir. Hal ini terutama terkait dengan pola diet tinggi garam sodium sehari-hari yang dimiliki oleh populasi penduduk di daerah tersebut. Konsumsi garam sodium > 5 gram/hari secara kronik akan meningkatkan risiko terjadinya hipertensi. Mengingat ikan laut secara alami memiliki kadar sodium yang cukup tinggi dan dapat mengalami peningkatan kadar sodium selama proses pengolahan, maka konsumsi ikan laut secara kron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This is also supported by previous research by Masengi et al, (2013) which showed that there was a significant relationship between seafood consumption and the incidence of hypertension (p=0.001). Research conducted by Rusliafa, et al (2014) in H. S. Harahap et al, (2022) shows that hypertension is more common in coastal communities. This is due to the high consumption of sodium in salted processed seafood.…”
Section: Consumption Of Seafoodmentioning
confidence: 95%
“…This is also supported by previous research by Masengi et al, (2013) which showed that there was a significant relationship between seafood consumption and the incidence of hypertension (p=0.001). Research conducted by Rusliafa, et al (2014) in H. S. Harahap et al, (2022) shows that hypertension is more common in coastal communities. This is due to the high consumption of sodium in salted processed seafood.…”
Section: Consumption Of Seafoodmentioning
confidence: 95%
“…Study shows that hypertension is often found in coastal areas. The high prevalence of hypertension in coastal areas cause by the high consumption of foods with high salt levels among coastal community, such as sea fish (Harahap et al, 2022;Saputra and Anam, 2016). One of the coastal areas on Lombok Island, West Nusa Tenggara, famous for its tourist areas, is Malimbu.…”
Section: Introductionmentioning
confidence: 99%
“…Based on research conducted by Harahap et al (2022) and Saputra (2016), besides consuming foods with high salt levels, there are several risk factors for hypertension among the coastal community.…”
Section: Introductionmentioning
confidence: 99%